Fitness - Archer, Jeff (Teach yourself--, 2006)
A do-it-yourself guide to getting fit, providing an introduction to the world of exercise, discussion of motivation, and a look at clothing and equipment, and including illustrated instructions for a variety of exercises, tips on formulating a fitness program and eating plan, and advice on maintaining the routine.